Acculturation in the Professional Activities of Specialists in International Relations - N. Romanenko (Vestnik MGIMO-Universiteta)
The article discusses the phenomenon of acculturation in the professional activities of international profile in terms of intercultural communication. The author emphasizes that acculturation problems related to intercultural communication have not only domestic but also international dimension. The article presents the theory and methodology of acculturation problems at different stages ofdevelopment of foreign and domestic scholars (specialists in cultural studies, ethnographers, ethnosociologists) and specifies the defference between the concepts of acculturation and assimilation of national and regional cultures. It further describes the strategy of acculturation (separation, marginalization, integration), emphasizes the role of integration strategy that makes it possible to preserve the cultural identity of a specialist in international relations along with an awareness of the regional culture of the host country. Special attention is given to the task of the university in preventing possible assimilation of future specialists in international relations and building "immunity" to the cultural (regional) adaptation and sustainable cultural identity as a representative the Russia. The article marks the mission of Russian culture as a medium of traditions, moral and spiritual values that built the Russian nation as a single community and state. The author writes that ethno-cultural component brings together many cultures, ethnic groups and nationalities of Russia, forms a common multicultural ground and brings about the need for cross-cultural awareness in international relations. That is confirmed by the State Federal Standard of Higher Education which describes specific competences that students of international relations are supposed to possess.